Making the Call: College Students’ Legal Consciousness and Hypothetical Activation of Police for Sexual Assaults - Oberweis, Trish (Violence against women, 2021)
Research has identified the necessity of sexual assault victims to label their experience as criminal to initiate reporting. However, barriers exist in labeling uninvited sexual contact as criminal. This study examined college students’ assessments of whether eight nonconsensual behaviors met the legal definition of sexual assault, and whether such behaviors should be reported to police. Results indicated students acknowledged the nonconsensual behaviors as criminal; however, gaps were identified between awareness that the acts were criminal and willingness to report to police. Findings demonstrate a need for continued efforts for sexual assault prevention among college students.